Murine homodimeric adhesion/growth-regulatory galectins-1, -2 and -7: comparative profiling of gene/ promoter sequences by database mining, of expression by RT-PCR/immunohistochemistry and of contact sites for carbohydrate ligands by computational chemistry - Lohr, M; Lensch, M; André, S; Kaltner, H; Siebert, H-C; Smetana, K; Sinowatz, F; Gabius, H-J (Folia biologica, 2007)
Following the detection of individual members of the family of galectins it is an obvious challenge to define the extent of functional overlap/divergence among these proteins. As a step to address this issue a comparative profiling has been started in the mouse as a model organism, combining sequence analysis, expression patterns and structural features in the cases of the homodimeric galectins-1, -2 and -7. Close relationship was apparent at the level of global gene organization. Scrutiny of the proximal promoter regions for putative transcription-factor-binding sites by two search algorithms uncovered qualitative and quantitative differences with potential to influence the combinatorial functionality of regulatory sequences. RT-PCR mapping with samples from an array of 17 organs revealed significant differences, separating rather ubiquitous gene expression of galectin-1 from the more restricted individual patterns of galectins-2 and -7. Using specific antisera obtained by affinity depletion including stringent controls to ascertain lack of cross-reactivity these results were corroborated at the level of galectin localization in fixed tissue sections. Nuclear presence was seen in the case of galectin-1. In addition to nonidentical expression profiles the mapping of the carbohydrate recognition domains of galectins-1 and -7 by homology modelling and docking of naturally occurring complex tetra- and pentasaccharides disclosed a series of sequence deviations which may underlie disparate affinities for cell surface glycans/glycomimetic peptides. In view of applicability the presented data can serve as useful reference to delineate changes with respect to disease and in genetically engineered models. To enable more general conclusions on the galectin network it is warranted to further pursue this combined approach within this lectin family.
Keywords: Molecular Sequence Data; galektiny; konformace sacharidů; messenger RNA; databáze nukleových kyselin; sekvence aminokyselin; Dimerization; Gene Expression Profiling; ligandy; orgánová specificita; výpočetní biologie; imunohistochemie; Gene Expression Regulation; Promoter Regions, Genetic; dimerizace; Carbohydrate Conformation; Galectins; Mice; Organ Specificity; Transcription Factors; regulace genové exprese; polymerázová řetězová reakce s reverzní transkripcí; sacharidy; sekvence nukleotidů; transkripční faktory; Base Sequence; Databases, Nucleic Acid; Immunohistochemistry; Ligands; RNA, Messenger; zvířata; Binding Sites; Amino Acid Sequence; myši; promotorové oblasti (genetika); Galectin 2; stanovení celkové genové exprese; galektin 2; Reverse Transcriptase Polymerase Chain Reaction; molekulární sekvence - údaje; galektin 1; Computational Biology; Galectin 1; vazebná místa; Carbohydrates; Animals